The In Vitro Screening of Drought Tolerant Potatoes (Solanum tuberosum L) of the Center for Tropical Horticulture Studies - IPB collections - Jane Kathryne Jolanda Laisina; Awang Maharijaya; Sobir Sobir; Agus Purwito (Jurnal Ilmu Pertanian Indonesia, 2021)
In supporting the replacement of potato varieties with the varieties that are adaptive to drought, effective and fast methods are needed. One of which is through in vitro screening of drought-tolerant genotypes. The aims of this research were to determine the appropriate concentration of sorbitol as a critical limit in the in vitro screening process of drought-tolerant genotypes, as well as to determine vegetative characteristics that could be used as indicators of in vitro selection and also to obtain in vitro drought-tolerant genotypes. To achieve these objectives, we used single-nodal explants of seven genotypes cultured for six weeks on MS media added with four levels of sorbitol concentration. Of the four treatments, sorbitol level that could distinguish susceptible and tolerant plants was 0.2 M sorbitol and at this concentration, the characteristics that showed significant interactions were plant height and root length, so that both characteristics could be used as selection indicators for the analysis of tolerance tests for the seven genotypes. The results of tolerance test using the analysis of relative decline and stress-susceptibility index (SSI) showed that PKHT4 and PKHT6 were the genotypes that were tolerant in vitro. Keywords: drought tolerant, in vitro, Solanum tuberosum, sorbitol